Human Impact Scale on the Preservation of Archaeological Sites from Mostiştea Valley (Romania) - Covătaru, Cristina; Stal, Cornelis; Florea, Mihai; Opriș, Ionela; Simion, Corina; Rădulescu, Ileana; Călin, Romeo; Ignat, Theodor; Ghiță, Cristina; Lazăr, Cătălin (Frontiers in Environmental Science, 2022)
Through time, both natural and cultural heritage have unfortunately been under threat due to multiple environmental and human-induced factors, which are likely to trigger various hazards such as soil erosion, landslides, or land collapse. The analysis of old cartographic material, aerial imagery, and satellite imagery has been used in multiple studies to observe and understand the changes that archaeological sites have undergone over the last centuries. These efforts are intended, among other things, to raise awareness of the threats affecting cultural heritage and to prevent and preserve tangible evidence of the distant past. In this study, historical maps and satellite images were analyzed to observe how the landscape in the Mostiștea Valley (Romania) has been used over the last 230 years and how this land use has affected the cultural heritage. Land cover and land use (LCLU) changes in the Mostiștea Valley have occurred due to numerous natural and anthropic forces. These changes have resulted in the damage of tangible heritage in the area with varying degrees of intensity. The results of this study allow the quantification of the magnitude of these changes and their impact on different sites in the region.